FEATURES OF MONETARY POLICY OF FOREIGN DEVELOPED COUNTRIES DURING THE PANDEMIC - T. A. Gorbacheva (Вестник университета)
The subject of the study is the financial system and monetary regulation of the economy during the COVID-19 coronavirus pandemic. The purpose of the article is to investigate the monetary policy pursued by the national Central banks of developed countries in the context of the economic crisis caused by pandemic. The paper uses comparative analysis, a systematic approach to the study of information, as well as graphical and tabular methods. The author considers monetary policy instruments used by national Central banks of developed countries to mitigate the impact of the pandemic on the real sector of the economy. The study reveals distinctive features of anti-crisis measures of monetary regulation bodies.